SIFAT VENIR DAN KAYU LAPIS LIMA JENIS KAYU HUTAN TANAMAN INDUSTRI - Memed Rozak; M I Iskandar; Paribotro Sutigno (Jurnal Penelitian Hasil Hutan, 1988)
Five  Indonesian wood species were investigated for their veneer  and plywood properties.    These species  include are  meranti merah  (Shorea  stenoptera  Burck.),   akasia (Acacia magnium  Willd.),  ampupu T (Eucalyptus urophylla), ampupu  A (Eucalyptus  urophylla) and ekaliptus  (Eucalvptus platiphvlla F.v.M).                    .                                                                             Four  wood species were peeled  in cold condition.  Only ekaliptus  was found  unsuitable  for peelling due  to high density and  the  interwoven nature  of  the fibers. Veneer  of 1.5 mm  thickness could be produced satistactorily at a cutting angle between 90o92°.                                                                                                                                                                                                    Average  shrinkage of  the  veneer  is  8.28%.  Average swelling  from oven dry  condition  to completely saturabed is 3.76%. Water resistance bonding  strength  for all wood  species studied  was m conformity   with the  Indonesian,  Japanese, and German standards.  Average thickness  reduction  due to pressing  pressure during plywood   making is  0,24 mm.               .Average  specific  gravity of  the plywood  appeared  to  0.048 be percent higher  than  that  of  the  wood  from  which they  are made of.